2008
DOI: 10.1021/jp077636y
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Surfactant and Hydrocarbon Aggregates on Graphite: A Molecular Dynamics Simulation Study

Abstract: We have examined the structure and dynamics of sodium dodecyl sulfate (SDS) and dodecane (C 12 ) molecular aggregates at varying surface coverages on the basal plane of graphite via classical molecular dynamics simulations. Our results suggest that graphite-hydrocarbon chain interactions favor specific molecular orientations at the single-molecule level via alignment of the tail along the crystallographic directions. This orientational bias is reduced greatly upon increasing the surface coverage for both mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 65 publications
8
69
0
Order By: Relevance
“…Similar findings have been reported for SDS monolayers. 27 In total, our findings on adsorption morphology changes with curvature above are in full aggreement with the MD simulations of Tummala et al on SDS behavior. 37 In their work, SDS formed micellar structures on planar substrate but positively curved substrate induced lamellar and negatively curved substrate cylindrical lamellar aggregates.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar findings have been reported for SDS monolayers. 27 In total, our findings on adsorption morphology changes with curvature above are in full aggreement with the MD simulations of Tummala et al on SDS behavior. 37 In their work, SDS formed micellar structures on planar substrate but positively curved substrate induced lamellar and negatively curved substrate cylindrical lamellar aggregates.…”
Section: Discussionsupporting
confidence: 91%
“…This results from the chain symmetry, and has been previously reported for, e.g., SDS in bulk and at interfaces. 27,68 Furthermore, the lipid head group interactions influence the lipid packing on the substrate. Simulations of HD isolate this effect as they represent just the tail interactions with the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, an important aspect of surface aggregation is overlooked: a surface is rarely, if ever, smooth and defect-free, and the presence of irregularities is expected to influence the aggregation process. Here, we continue our studies of sodium dodecyl sulfate (SDS) and hydrocarbon aggregation on an ideal graphite surface 1 by focusing on the effects of surface defects (vacancies and steps) on the aggregation kinetics of SDS and dodecane (C 12 ) monolayers at varying coverages on graphite.…”
Section: Introductionmentioning
confidence: 99%
“…So far, however, a satisfactory computational method has not been demonstrated for a system large enough to exhibit the micelle formation and orientation. [8][9][10] To treat the same system at the micellar (colloidal) length scale with a simpler approach, we recently chose to view a micelle as a macroscopic "rod" and have shown that anisotropic van der Waals torque between rod-like surfactant micelles and a graphite substrate is large enough to orient the micelles perpendicular to the symmetry axes of the graphite lattice. 11,12 In more recent experiments, we also studied the aggregates of sodium dodecyl sulfate (SDS) on Au(111), a system that is well-known 7,13 to recognize the lattice symmetry axes.…”
Section: Introductionmentioning
confidence: 99%